Asian University Presses in the Digital Age - Kratoska, Paul (International Higher Education, 2010)
University presses in Asia and the West publish scholarly material, with limited commercial appeal, and face common problems arising from falling sales, rising costs, and the shift to electronic media for teaching materials. However, in North America a large number of presses are competing for a shrinking market, while Asia represents a growing market, especially for English-language publishing. Electronic publications have begun to appear in the region, but their effects are difficult to predict.